ANALISIS CLUSTER TERHADAP TINDAKAN KEKERASAN DI INDONESIA DENGAN ALGORITMA CLUSTER HIRARKI MENGGUNAKAN METODE WARD - Muhammad Taufiqurahman Alghani; Marhaeni Marhaeni (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2023)
This research was motivated by the virality of cases of acts of violence by artists or public figures in 2022. The prevalence of these acts of violence shows that the Indonesian people are very opposed to acts of violence so that this research can formulate how the level of acts of violence occurred in all provinces in Indonesia . The purpose of this study was to carry out the process of grouping provinces based on the environmental categories where acts of violence occurred. This study will analyze 34 provinces in Indonesia using the hierarchical cluster method. The results obtained from this study are able to determine the level of security and the condition of security and order in all provinces in Indonesia.